2000
DOI: 10.1108/08858620010316813
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between suppliers and customers through relationship promoters: theoretical considerations and empirical results

Abstract: Despite the pivotal importance of marketing‐oriented boundary spanners for successful relationship development, only a few studies have investigated the influence of these boundary spanners on relationship outcomes. Findings of this study show that relationship advancement through a relationship promoter in the supplier or customer firm have a positive significant impact on the growth of sales within the relationship and the supplier’s share of a customer’s business. Relationship promoters are persons who iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 89 publications
(98 reference statements)
3
76
0
2
Order By: Relevance
“…Moreover, empathy, resulting from identification on the basis of shared categories concerning the motives and conditions of behaviour, including sources of cooperation, affects both one's own trustworthiness (in the willingness to make sacrifices for others), and one's trust (in the tolerance of behaviour that deviates from expectations) (Palmer & Bejou, 1994;Walter & Gemunden, 2000). When parties share values and an affective attachment, they can also be expected to develop commitment for each other (Achrol, 1997).…”
Section: Relationship Performance and Organizational Cultural Differementioning
confidence: 98%
“…Moreover, empathy, resulting from identification on the basis of shared categories concerning the motives and conditions of behaviour, including sources of cooperation, affects both one's own trustworthiness (in the willingness to make sacrifices for others), and one's trust (in the tolerance of behaviour that deviates from expectations) (Palmer & Bejou, 1994;Walter & Gemunden, 2000). When parties share values and an affective attachment, they can also be expected to develop commitment for each other (Achrol, 1997).…”
Section: Relationship Performance and Organizational Cultural Differementioning
confidence: 98%
“…Research on the boundary spanning role of frontline employees has concentrated on the employee and concepts such as role conflict, ambiguity and job satisfaction (e. g. Bettencourt and Brown 2003;de Jong et al 2004;Singh et al 1996) or their influence on customer relationships (Biong and Selnes 1996). Studies by Walter (1999), Walter and Gemünden (2000), and have shown that frontline employees as boundary spanning relationship promoters also play an important role in interorganizational exchange processes and thereby facilitate the innovativeness of their company. Our findings offer further empirical support for the importance of boundary spanning frontline employees as a resource for innovation.…”
Section: Discussionmentioning
confidence: 97%
“…As marketing-oriented boundary spanners (Walter and Gemünden 2000), frontline employees play a crucial part in developing and maintaining customer relationships (Biong and Selnes 1996). Ideally, they act as relationship promoters and facilitate interorganizational exchange processes through personal relationships (Walter 1999).…”
Section: Evidence From Research On Boundary Spanningmentioning
confidence: 99%
“…Purchase (2000) proposes the concept of network catalyst as one who initiates relationship development between network actors without themselves becoming closely involved in relationship development. Other researchers have developed the concept of relationship promoters working from within an organization with other network actors (Walter & Gemunden, 2000). In contrast, the NC serves as a catalyst who builds new linkages among multiple firms at multiple levels and who must interact with different actors for the adoption of a new process (Chakrabarti, 1974).…”
Section: From Lead Users To Network Championsmentioning
confidence: 97%